Application of whey protein microparticulates in the production of ice cream and other dairy products - P. B. Sitnikova; N. V. Kazakova (Пищевые системы)
The aim of this paper is to systemize data on the use of whey protein microparticulates (WPMP) in production of ice cream and other dairy products. Information about the essence of the microparticulation process and methods for WPMP production is given. Data on the composition and physico-chemical properties of liquid and dry WPMP are presented. An effect of sizes of WPMP particles on quality characteristics of products made with their use is described. The majority of the analyzed studies indicate that the diameter of particles is 1.0–2.5 µm. However, contradictory data were obtained for this indicator — if the results of all studies are taken into consideration, a size of conglomerates can be 0.5 to 12 µm. These sizes are comparable with parameters of fat globules, which allow receptors of the human oral cavity to perceive them identically. Due to this, WPMP can be used as an imitator of milk fat. It is noted that the microparticulation process enables producing WPMP with targeted functional properties, namely, with particular characteristics by indicators “solubility”, “water holding capacity”, “gel formation”, “emulsifying and foam forming properties”. Information about the specific features of using and dosing WPMP in fermented milk products, such yogurt, kefir, curd cheese and cheese, is given. A special attention is paid to the results of the investigation of using WPMP in ice cream. It is noted that most often scientists used WPMP to make up for the sensation of fatness in defatted and nonfat dairy products. The ability of WPMP to increase the biological value of food products is highlighted. It has been concluded that WPMP enables formation of soft and elastic structure in low-fat dairy products, intensification of milky color and restriction of ice crystal growth in frozen desserts by binding and equally distributing moisture. The data were obtained about the clinical investigation of an effect of ice cream with WPMP on the health of children and adults. The negative effect of WPMP on the indicators of clinical analyses of humans and their health was not revealed.